SBN60, strontium-barium niobate at 100 K - Stachowicz, Marcin (International Union of Crystallography, 2013)
The title compound, Sr(0.6)Ba(0.4)Nb(2)O(6) (strontium barium niobium oxide), belongs to the group of strontium–barium niobates with varying composition of Sr and Ba. Their general formula can be written as Sr(x)Ba(1 - x)Nb(2)O(6). Below the Curie temperature, T (c), these materials indicate ferroelectric properties. The Curie temperature for SBN60 is equal to 346±0.5 K so the structure is in the ferroelectric phase at the measurement temperature of 100 K. Characteristic for this family of compounds is the packing along the z-axis. The NbO(6) corner-sharing octahedra surround three types of vacancy tunnels with pentagonal, square and triangular shapes. The Sr(2+) ions partially occupy two unique sites, the first one located inside the pentagon and the second one in the square tunnels. Consequently, they are situated on the mirror plane and the intersection of two glide planes, respectively. The site inside the pentagonal tunnel is additionally disordered so that the same position is shared by Ba(2+) and Sr(2+) ions whereas another part of the Ba(2+) ion occupies a different position (relative occupancies 0.43:0.41:0.16). One of the Nb(V) atoms and three of the O(2−) ions occupy general positions. The second Nb(V) atom is located on the intersection of the mirror planes. Two remaining O(2−) ions are located on the same mirror plane. Only the Nb(V) atom and one of the O(2−) ions which is located on the mirror plane are not disordered. Each of the remaining O(2−) ions is split between two sites, with relative occupancies of 0.52:0.48 (O(2−) ions in general positions) and 0.64:0.36 (O(2−) ion on the mirror plane).